2015
DOI: 10.4102/sajip.v41i1.1133
|View full text |Cite
|
Sign up to set email alerts
|

The influence of emotional intelligence and trust on servant leadership

Abstract: Orientation: Constructs were explored from a positive organisational behaviour (POB)paradigm. The aim of POB constructs is to develop and improve employees’ psychological strengths, well-being and performance.Research purpose: The objective of this research was to investigate the relationships between servant leadership, emotional intelligence and trust in the manager. A model depicting a sequential process of interrelationships amongst the constructs was proposed.Motivation for the study: Organisations worldw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 43 publications
2
25
0
1
Order By: Relevance
“…There is a rich literature on supervisor trait emotional intelligence supporting its function as a resource at work. For example, managers' trait EI predicted trust from their employees (Du Plessis, Wakelin, & Nel, 2015) and trust and job satisfaction mediated the relationship between supervisor trait EI and project success (Rezvani, Chang, Wiewiora, Ashkanasy, Jordan, & Zolin, 2016). Similarly, Huang, Chan, Lam, and Nan (2010) found that lower burnout mediated the link between trait EI and work performance in a telecommunications call center.…”
Section: Defining Emotional Intelligencementioning
confidence: 99%
“…There is a rich literature on supervisor trait emotional intelligence supporting its function as a resource at work. For example, managers' trait EI predicted trust from their employees (Du Plessis, Wakelin, & Nel, 2015) and trust and job satisfaction mediated the relationship between supervisor trait EI and project success (Rezvani, Chang, Wiewiora, Ashkanasy, Jordan, & Zolin, 2016). Similarly, Huang, Chan, Lam, and Nan (2010) found that lower burnout mediated the link between trait EI and work performance in a telecommunications call center.…”
Section: Defining Emotional Intelligencementioning
confidence: 99%
“…This study is positioned within the rising field of positive organisational behaviour (POB) or positive organisational scholarship (POS), which has emerged from the positive psychology movement (Donaldson & Ko, 2010). Various studies have been undertaken in the field of POB in South Africa and abroad, such as those by Beal, Stavros and Cole (2013);De Waal and Piennar (2013); Simons and Buitendach (2013); Eustace and Martins (2014); Geldenhuys, Łaba and Venter (2014) and Du Plessis, Wakelin and Nel (2015). These studies focused on constructs such as PsyCap, work engagement, intention to quit, organisational commitment and others.…”
Section: Introductionmentioning
confidence: 99%
“…Por exemplo, o comprometimento organizacional (Morris, 2013), desempenho (Choudhary et al, 2013), efetividade em equipes de trabalho (Mahembe & Engelbrecht, 2014), engajamento no trabalho (Villiers, 2015), criatividade e inovação (Yoshida, Sendjays, Hirst, & Cooper, 2014), inteligência emocional (Barbuto, Gottfredson, & Searle, 2014;Plessis, Wakelin, & Nel, 2015) e comportamentos proativos (Hunter et al, 2013).…”
Section: Discussionunclassified